PENGARUH METODE PROBLEM SOLVING TERHADAP PEMBELAJARAN PASSING BAWAH BOLA VOLI - Ikmal, Ikmal; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractA research of the impact of Problem Solving method conducted on the students IX class SMA Negeri 4 Singkawang to find out the impact on Volleyball Passing-Down Learning. The method of this research is pre-experimental method with the approach one group pre-test - post-test design and the sample were 32 students from IX class SMA Negeri 4 Singkawang. The technique of data analysis was Normalitas test, Homogenitas test, and T-test. The finding of the research revealed the ratio between pre-test result with the avarage 13,34 and post-test result with the avarage 18,03 was increased to 4,69 with the improvement percentage 34,97%, and T-test result 5,318 bigger than T-table in the amount of 1,695. Based on the research findings, there was a impact of using Problem Solving method on Volleyball Passing-Down Learning on the students IX class SMA Negeri 4 Singkawang with the improvement of Volleyball Passing-Down skills.Keywords: Impact, Problem Solving Method, Volleyball Passing-Down, Experimental